Growth Characteristics of a Collection of Vegetatively Propagated Cherry and Plum Cuttings in the Nursery - Azamovna , Kimsanova Kholida; Nodirbek’s, Rahmatov Mirjalal (Miasto Przyszłości, 2024)
Studies conducted on cherry and plum grafts have shown that the diameter of the stem of cherry and plum grafts grown from seed at the time of bud grafting.